MINAT SISWI SMA DR. SOETOMO SURABAYA PADA KEGIATAN EKSTRAKURIKULER FUTSAL - HALIM, S.ROHMAN (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In globalization era, education is the most integral part which should be taken to can in competition with other countries. Sport is systematic all activity to motivated, build and develop physical, spiritual, and social potential. Futsal is one of the sport the most had a great vogue. Interest is a high trend and fervor or avidity to something. Research question of this research are: how is SMA Dr. Soetomo Surabaya schoolgirl interest at activity futsal extracurricular and what factor interest is the most dominant which is had by them in joining activity futsal extracurricular. This research is quantitative approach and descriptive research. Instrument this research is questionnaire. Based on the questionnaire result, each one of indicators result i.e. indicator of avidity to join activity futsal extracurricular is 398, indicator of futsal extracurricular perception is 916, indicator of feeling in joining the activity is 494, and indicator of purpose in joining the activity is 243. Grand total result indicate that SMA Dr. Soetomo Surabaya schoolgirl interest at activity futsal extracurricular is 2051 and average 147 (very high). Indicator factor interest the most dominant which is had by them in joining activity futsal extracurricular is indicator of futsal extracurricular perception. All of these indicate that futsal extracurricular perception in SMA Dr. Soetomo Surabaya is very high with final result is 916 and percentage 37,39%. The conclusion of this research is SMA Dr. Soetomo Surabaya schoolgirl interest at activity futsal extracurricular is very high. Keywords: schoolgirl interest and futsal extracurricular.